Assesment of Kinetic Parameters for Thermophilic Anaerobic Contact Reactor Treating Food-Processing Wastewater - Senturk, E.; Ynce, M.; Onkal Engin, G. (Springer International Publishing Ag, 2013)
A thermophilic anaerobic contact reactor for the treatment of potato-processing wastewaters was designed as a continuous-flow, completely-mixed homogeneous system. The reactor was operated at ten different organic loading rates ranging from 0.84 g COD/L.d to 7.00 g COD/L.d for a duration of approximately 250 days. The fundamental way to maintain optimum operating conditions of anaerobic digestion systems is to have a well acquaintance with the dynamic behaviours of the process. For this purpose, different types of kinetic models were used in this study, namely the substrate balance, the maximum / specific substrate utilization rate and the methane production rate models. The experimental data obtained indicated that the models used were all applicable for the description of bio-kinetic behaviour of the thermophilic anaerobic contact reactor.
Keywords: Thermophilic; Anaerobic; Kinetic evaluation; Organic loading rate; Potato-processing wastewaters